THE SPANISH FLU PANDEMIC – A LESSON NOT LEARNED (Annual of the Faculty of Philosophy in Skopje, 2021)
The Covid-19 pandemic that began last year inevitably prompted scientists to look back at the last major Spanish flu pandemic that occurred a century ago, sweeping across the globe and contributing to massive human losses from which some nations had to recover. Much like today, the threat of the Spanish flu was initially underestimated, most likely due to the hostilities happening as a result of WWI. The War ended, but the virus evolved from an epidemic to a major, unprecedented pandemic. Authorities reacted slowly to the spread of the flu, and the health system was completely unprepared to deal with the new and unknown danger. At first, even doctors, virologists, and epidemiologists could not come to terms with the type of virus they were dealing with. However, as the pandemic spread, the world adapted to the new conditions. States and local authorities introduced a series of restrictive measures to prevent the spread of the virus, hygiene measures were tightened, and there were orders for the mandatory wearing of masks, as well as the closure of shops, and cultural and educational institutions. There are many points that are similar from the time of the Spanish flu pandemic to today’s conditions related to Covid-19. Just as it had unexpectedly appeared in 1918, the Spanish flu disappeared in 1920. It took scientists more than a decade after the end of the pandemic to discover the cause of the outbreak, but even today there are still many unknowns related to the Spanish flu.